Audit of amniocentesis from a district general hospital: is it worth it?. Issue 6734 (12th May 1990) - Wiener, J J; Farrow, A; Farrow, S C
Abstract : OBJECTIVE–To audit all mid-trimester amniocenteses performed by obstetricians at a district general hospital to see whether experience improved the outcome. DESIGN–Retrospective review of medical records. SETTING–Royal Gwent Hospital, south Wales. SUBJECTS–All 469 amniocenteses carried out in 1985-7. OUTCOME MEASURES–Number of attempts at withdrawal of amniotic fluid; number with bloodstained liquor; and number of subsequent miscarriages, terminations, and congenital abnormalities. RESULTS–Of the 469 amniocenteses, 411 were performed by one obstetrician, and initial comparisons with those performed by the rest of the hospital team showed no significant differences in outcome of pregnancy. The main difference between the two groups was in the number of attempts at withdrawal of amniotic fluid and the number with bloodstained liquor. The single obstetrician failed to obtain amniotic fluid on 1% of occasions compared with 10% for the other operators by the end of the second attempt. The costs of carrying out the audit were considerable. The review of fewer than 500 case records cost the equivalent of 2000 pounds in staff time and took over 200 hours to complete, equivalent to 63 sessions of one person's time. CONCLUSIONS–The audit was useful in that it provided information on complication rates, which could be compared with published data, and comparisons between obstetricians who perform large and small numbers of procedures. IMPLICATIONS–For an individual's practice the monitoring of amniocentesis should not be continuously carried out and subsequent audits should tackle other common procedures. When an audit is attempted the health service should provide adequate support to clinicians for this purpose.